A single seizure selectively impairs hippocampal‐dependent memory and is associated with alterations in PI3K/Akt/mTOR and FMRP signaling. Issue 4 (28th October 2018) - Holley, Andrew J.; Hodges, Samantha L.; Nolan, Suzanne O.; Binder, Matthew; Okoh, James T.; Ackerman, Kaylin; Tomac, Lindsey A.; Lugo, Joaquin N.
Summary: Objective: A single brief seizure before learning leads to spatial and contextual memory impairment in rodents without chronic epilepsy. These results suggest that memory can be impacted by seizure activity in the absence of epilepsy pathology. In this study, we investigated the types of memory affected by a seizure and the time course of impairment. We also examined alterations to mammalian target of rapamycin (mTOR) and fragile X mental retardation protein (FMRP) signaling, which modulate elements of the synapse and may underlie impairment. Methods: We induced a single seizure and investigated hippocampal and nonhippocampal memory using trace fear conditioning, novel object recognition (NOR), and accelerating rotarod to determine the specificity of impairment in mice. We used western blot analysis to examine for changes to cellular signaling and synaptic proteins 1 h, 24 h, and 1 week after a seizure. We also included a histologic examination to determine if cell loss or gross lesions might alternatively explain memory deficits. Results: Behavioral results indicated that a seizure before learning leads to impairment of trace fear memory that worsens over time. In contrast, nonhippocampal memory was unaffected by a seizure in the NOR and rotarod tasks. Western analysis indicated increased hippocampal phospho‐S6 and total FMRP 1 h following a seizure. Tissue taken 24 h after a seizure indicated increased hippocampal GluA1, suggesting increased α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor expression. Histologic analysis indicated that neither cell loss nor lesions are present after a single seizure. Significance: The presence of memory impairment in the absence of damage suggests that memory impairment caused by seizure activity differs from general memory impairment in epilepsy. Instead, memory impairment after a single seizure is associated with alterations to mTOR and FMRP signaling, which leads to a disruption of synaptic proteins involved in consolidation of long‐term memory. These results have implications for understanding memory impairment in epilepsy.